Menumbuhkan Sense of Belonging dan Jiwa Pemipin Siap Menghadapi Perubahan Organisasi - Retnowati, Ayu Nike; Simarmata, Harianto (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2023)
Student association is a forum that facilitates students to be able to express their aspirations and creativity. Student association is expected to be a learning medium for each student to be able to hone their organizational skills and stimulate their socializing and decision-making abilities. Over time, with the high level of student activities in the academic field, student associations have become uninteresting to follow. Some students only use them as a means to gather by abandoning their main purpose. Ironically, only some members adhere to the Vision-Mission that has been made and other members only assume that realizing the Vision-Mission is the obligation of the association's management. This view hampers the cadre process. This arises because there is a feeling of lack of self-confidence, slow adaptation to a new environment and a feeling of fear in acting/worrying about making mistakes. In this Community Service activity, it will be carried out for UNIBI management student association partners (Excma UNIBI), with the theme "Growing a Sense of Belonging and Creating a Leader's Soul Ready to Face Organizational Change". This activity aims to foster a new spirit for members and administrators of the association to be able to build the association as a shared responsibility of all members of the association. This PKM is conducted using interactive methods, learning experiences to help participants reflect on the current state of the organization as a bridge to make organizational changes and implement efective Leadership style.